Guide to quantitative research writing : research 2 - Thesally T. Dalisay (Quezon City : Brilliant Creations Publishing, Inc., 2022)
"The lessons in each unit of this textbook are specifically crafted to guide the learners in understanding the rigors of quantitative research. Through in depth discussion, authentic examples and developmental activities, the learners will be able to have meaningful learning experiences as they grasp the concepts needed when completing a quantitative research study."
Includes references and bibliography.
English text.
Keywords: Research; Quantitative research